Matrix mechanical plasticity regulates cancer cell migration through confining microenvironments - Katrina M. Wisdom (Nature Portfolio, 2018)
In order to metastasize, cancer cells must migrate through basement membranes and dense stroma, and proteases are thought to be required due to the confining nature of these matrices. Here the authors use synthetic matrices to show that cells can migrate through confining matrices using force generation alone, rather than protease degradation, if the matrices exhibit mechanical plasticity.